2023
DOI: 10.3390/molecules28093821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HAT-CN Layer Thickness on Molecular Orientation and Energy-Level Alignment with ZnPc

Abstract: Efficient energy-level alignment is crucial for achieving high performance in organic electronic devices. Because the electronic structure of an organic semiconductor is significantly influenced by its molecular orientation, comprehensively understanding the molecular orientation and electronic structure of the organic layer is essential. In this study, we investigated the interface between a 1,4,5,8,9,11-hexaazatriphenylene hexacarbonitrile (HAT-CN) hole injection layer and a zinc-phthalocyanine (ZnPc) p-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The HOMO level of the HTL can be further decreased by increasing the thickness of the MoO 3 HIL. A recent study reported that a sufficiently thick layer is necessary to decrease the HOMO level of an HTL with a 1,4,5,8,9,11hexaazatriphenylene hexacarbonitrile (HAT-CN) HIL, which has an electronic structure similar to that of the MoO 3 HIL [14]. This highlights the importance of understanding the energy-level alignment with different thicknesses of the MoO 3 HIL in formulating a strategy to further enhance OLED performance.…”
Section: Introductionmentioning
confidence: 99%
“…The HOMO level of the HTL can be further decreased by increasing the thickness of the MoO 3 HIL. A recent study reported that a sufficiently thick layer is necessary to decrease the HOMO level of an HTL with a 1,4,5,8,9,11hexaazatriphenylene hexacarbonitrile (HAT-CN) HIL, which has an electronic structure similar to that of the MoO 3 HIL [14]. This highlights the importance of understanding the energy-level alignment with different thicknesses of the MoO 3 HIL in formulating a strategy to further enhance OLED performance.…”
Section: Introductionmentioning
confidence: 99%